A SEMIOTIC INTERPRETATION OF ORNAMENTS IN LAPO BATAK IN MEDAN - Elizabeth, Windy Lizasadela; Zainuddin, Zainuddin; Murni, Sri Minda (TRANSFORM: Journal of English Language Teaching and Learning, 2020)
This study aims to analyze the semiotic meaning in Lapo Batak ornaments in Medan. The data of this study were taken from the interpretation of Batak Toba people who live in Medan in interpreting their cultural symbols. In analyzing the data, the research was conducted by using qualitative method. The result showed the semiotic meaning and how the cultural values were realized in Lapo Batak ornaments. The data were analyzed by using Roland Barthes™ order of signification theory; denotation, connotation, and myth to emphasize the interaction between the sign with the personal cultural experience of the viewers, and the interaction between convention in the sign with the conventions experienced and expected by viewers. The researcher found that the interpretations of the personal cultural experience from the viewers were still far from the Batak Toba convention (myth) in interpreting the ornaments.